The Orange Fairy Book - Lang, Andrew, 1844-1912 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Orange Fairy Book" by Andrew Lang is a collection of enchanting fairy tales compiled and edited during the late 19th century. This volume features vibrant narratives from various cultures, adapting traditional folklore into child-friendly stories that celebrate themes of courage, cunning, and morality. Each tale blends fantasy with moral lessons, making it a delightful read for children and adults alike. At the start of this collection, the preface outlines the purpose and origins of the stories, revealing that they have been gathered from oral traditions across different cultures, including African and Native American lore. The first story introduces Makoma, a hero from the town of Senna, who showcases extraordinary strength and bravery by confronting crocodiles and giants. He embarks on a journey of self-discovery and adventure, overcoming formidable foes while gathering strength and allies along the way. The opening sets the tone for the captivating tales that follow, inviting readers into a world rich with imagination and moral teachings. (This is an automatically generated summary.)
The Story of the Hero Makoma -- The Magic Mirror From the Senna -- Story of the King Who Would See Paradise -- How Isuro the Rabbit Tricked Gudu -- Ian, the Soldier's Son -- The Fox and the Wolf -- How Ian Direach Got the Blue Falcon -- The Ugly Duckling -- The Two Caskets -- The Goldsmith's Fortune -- The Enchanted Wreath -- The Foolish Weaver -- The Clever Cat -- The Story of Manus -- Pinkel the Thief -- The Adventures of a Jackal -- The Adventures of the Jackal's Eldest Son -- The Adventures of the Younger Son of the Jackal -- The Three Treasures of the Giants -- The Rover of the Plain -- The White Doe -- The Girl-Fish -- The Owl and the Eagle -- The Frog and the Lion Fairy -- The Adventures of Covan the Brown-haired -- The Princess Bella-Flor-- The Bird of Truth -- The Mink and the Wolf -- Adventures of an Indian Brave -- How the Stalos were Tricked -- Andras Baive -- The White Slipper -- The Magic Book.
Release date is 2002-01-01
Keywords: Fairy tales; Folklore